Measuring Perceived Quality of Life to Assess Health Needs among People with MS: A Community Study in Derbyshire, UK - R Vazirinejad; JM Lilley (Tehran University of Medical Sciences, 2008)
Background: To determine the health needs of people with multiple sclerosis living in the Southern Derbyshire region of the UK, using a quality of life postal questionnaire. Methods: This was a population-based survey using a postal questionnaire comprising the 54-item Multiple Sclerosis Quality of life questionnaire (MSQOL-54), Nottingham Extended Activities of Daily Living (ADL), and some additional demographic questions. A postal questionnaire was sent via 40 health practices (50% of general practitioners) in Southern Derbyshire to all patients diagnosed with Multiple Sclerosis confirmed by a neurologist. Results: Two hundred and one completed questionnaires (from 223 respondents) were returned using pre-paid postage. Respondents were divided into those with mild (41%), moderate (36%) and severe (23%) disability on the basis of their ADL scores. Seventy seven percent (155) of respondents were women. The POQL mean scores for three groups of mild, moderate and severe disability were 12.0±2.8, 9.5±3.0, and 8.0±3.5 (out of 17), respectively. The regression model showed a relationship between disability scores and POQL scores (Beta=0.58, P= 0.000). Conclusion: For the three groups of disabled people, different priorities emerged in relation to POQL, indicating that services seeking to improve quality of life in these groups must identify and target the relevant issues appropriately and be sensitive to the differing requirements reported by individuals at different levels of disability. Studies of this type are becoming increasingly important for determining which outcomes should be measured when evaluating interventions designed to maintain well-being and protect the health of patients with MS.